State formation in early modern England, c. 1550-1700 - Braddick, Michael (Cambridge University, 2013)
On the basis of a wide-ranging synthesis of work in diverse fields of English, British and colonial history, this book makes a novel argument about the modernisation of the seventeenth-century English state. It also focuses on the role of class and gender interests in the state's development.